Geological and Geochemical Controls on Subsurface Microbial Life in the Samail Ophiolite, Oman - Rempfert, Kaitlin R.; Miller, Hannah M.; Bompard, Nicolas; Nothaft, Daniel; Matter, Juerg M.; Kelemen, Peter; Fierer, Noah; Templeton, Alexis S. (Frontiers in Microbiology, 2017)
Microbial abundance and diversity in deep subsurface environments is dependent upon the availability of energy and carbon. However, supplies of oxidants and reductants capable of sustaining life within mafic and ultramafic continental aquifers undergoing low-temperature water-rock reaction are relatively unknown. We conducted an extensive analysis of the geochemistry and microbial communities recovered from fluids sampled from boreholes hosted in peridotite and gabbro in the Tayin block of the Samail Ophiolite in the Sultanate of Oman. The geochemical compositions of subsurface fluids in the ophiolite are highly variable, reflecting differences in host rock composition and the extent of fluid-rock interaction. Principal component analysis of fluid geochemistry, along with geologic context indicate the presence of at least four fluid types in the Samail Ophiolite (“gabbro”, “alkaline peridotite”, “hyperalkaline peridotite”, and “gabbro/peridotite contact”) that vary strongly in pH and the concentration of H2, CH4, Ca2+, Mg2+, NO3-, SO42-, trace metals, and DIC. Geochemistry of fluids is strongly correlated with microbial community composition; similar microbial assemblages group according to fluid type. Hyperalkaline fluids exhibit low diversity and are dominated by taxa related to the Deinococcus-Thermus genus Meiothermus, candidate phyla OP1, and the family Thermodesulfovibrionaceae. Gabbro- and alkaline peridotite- aquifers harbor more diverse communities and contain abundant microbial taxa affiliated with Nitrospira, Nitrosospharaceae, OP3, Parvarcheota, and OP1 order Acetothermales. Wells that sit at the contact between gabbro and peridotite host microbial communities distinct from all other fluid types, with an enrichment in betaproteobacterial taxa. Together the taxonomic information and geochemical data suggest that several metabolisms may be operative in subsurface fluids, including methanogenesis, acetogenesis, and fermentation, as well as the oxidation of methane, hydrogen and small molecular weight organic acids utilizing nitrate and sulfate as electron acceptors. Dynamic nitrogen cycling may be especially prevalent in gabbro and alkaline peridotite fluids. These data suggest water-rock reaction, as controlled by lithology and hydrogeology, constrains the distribution of life in terrestrial ophiolites.